Challenges and Strategies of Waste Management by Makassar Government - Nggilu, Rukiah (Poltekkes Kemenkes Tasikmalaya, 2025)
This study aims to analyze the challenges and strategies of waste management by the Makassar City Government. The method used is a qualitative approach with data collection techniques through observation, in-depth interviews with cleaners, Environmental Service staff, waste bank managers, and residents, and documentation of related policies. This study was conducted in several sub-districts in Makassar City that are the focus of waste management, such as Panakkukang, Tamalate, and Manggala. The results of the study indicate that waste management in Makassar City still faces various challenges, including low public awareness in sorting waste, limited transportation fleets and personnel, and the capacity of the Antang Final Disposal Site (TPA) which is almost full. In addition, community participation in programs such as waste banks and TPS 3R is still low. In terms of policy, although Regional Regulations have been issued, weak supervision and law enforcement are the main obstacles. However, the Makassar City Government has implemented various strategies such as involving technology through the